Bir Sesüstü Lülen İn Tasarimi Ve Akişin Sayisal Olarak İncelenmesi - Cosar, Ilker; Duranay, Mehmet (Institute of Electrical and Electronics Engineers Inc., 2019)
In this study, in order to obtain supersonic flow in different converging-diverging nozzles a numerical study was conducted to find parameters which form necessary nozzle profiles.ANSYS CFX software package program was used for the numerical study. Air was chosen as a working fluid (Pr = 0.718). Taking nozzle geometries as a) circular cross-section converging-diverging nozzle, b) quadratic cross-section converging-diverging nozzle, c) converging part with circular cross-section and diverging part with quadratic cross-section nozzle (mixed nozzle), flow analyses were carried out. In order to verify the results, a similar study from the literature was taken into account and same parameters were used. Both analytical and numerical results obtained were compared with literature and a good agreement was found. In order to show grid-free solution, three type of grids were used and a suitable one was chosen. Further, two turbulence model was tried and the best solutions were obtained by SST model.Throughout the study, at the inlet pressure was 7 bar in the outlet atmospheric pressure (1 bar) was accepted. The results obtained were presented graphically in terms of parameters such as velocity, pressure, density, Mach number and temperature. The results were evaluated and mixed nozzle was found as an optimum nozzle. © 2019 IEEE.
3rd International Symposium on Multidisciplinary Studies and Innovative Technologies, ISMSIT 2019 -- 11 October 2019 through 13 October 2019 -- Ankara -- 156063
Keywords: Converging-Diverging Nozzle; Nozzle Design; Supersonic Flow; Thermodynamic Analysis